Technical advancements in epigenomics and applications in transplantation. Issue 1 (February 2021) - Kuscu, Canan; Eason, James D.; Kuscu, Cem
Abstract : Purpose of review: To summarize recently developed next generation sequencing-based methods to study epigenomics and epitranscriptomics. To elucidate the potential applications of these recently developed methods in transplantation research. Recent findings: There are several methods established with the collaborative efforts from different consortiums, such as ENCODE, Human Cell Atlas, and exRNA consortium to study role of epigenetics in human health. Rapid development in the sequencing technology also enabled the establishment of these genome-wide studies. This review specifically focuses on these techniques, such as EM-seq to study DNA methylation, CUT&RUN, and CUT&Tag to study histone/transcription factor--DNA interactions, ATAC-seq to study chromatin accessibility, Hi-C to explore 3D genome architecture and several methods to study epigenetics at single-cell level. In addition, we briefly mentioned recent efforts to study lncRNAs and extracellular miRNAs. Summary: Technical advancements in genomics, particularly epigenomics, shed light on the role of epigenetics and recently epitranscriptomics in different fields. Application of those techniques to transplantation research is still very limited because of technical limitations. On the other hand, there are a lot of promising studies showing that these new techniques can be adapted to study the molecular biology of transplant-related problems.